External and Internal Reshaping of Plant Thermomorphogenesis. (August 2021) - Park, Young-Joon; Kim, Jae Young; Lee, June-Hee; Han, Shin-Hee; Park, Chung-Mo
Abstract : Plants dynamically adapt to changing temperatures to ensure propagation and reproductive success, among which morphogenic responses to warm temperatures have been extensively studied in recent years. As readily inferred from the cyclic co-oscillations of environmental cues in nature, plant thermomorphogenesis is coordinately reshaped by various external conditions. Accumulating evidence supports that internal and developmental cues also contribute to harmonizing thermomorphogenic responses. The external and internal reshaping of thermomorphogenesis is facilitated by versatile temperature sensing and interorgan communication processes, circadian and photoperiodic gating of thermomorphogenic behaviors, and their metabolic coordination. Here, we discuss recent advances in plant thermal responses with focus on the diel and seasonal reshaping of thermomorphogenesis and briefly explore its application to developing climate-smart crops. Highlights: Multiple thermosensors and thermosensory mechanisms, including biophysical thermosensors, have distinct and overlapping roles in triggering an array of thermomorphogenic responses in plants. Diverse temperature signaling molecules are actively transmitted through interorgan communication routes to synchronize thermomorphogenic responses in plant organs. Plant thermomorphogenesis is precisely gated by the circadian clock to help plants stimulate thermos-adaptive behaviors at the most favorable time point of the day. Plants integrate daylength and temperature information into the circadian clock to aptly shape thermomorphogenic growth under diel and seasonal fluctuations. Plant thermomorphogenesis is extensively reshaped by endogenous metabolic signals, which largely depend on photosynthetic performance and soil environments.